2020
DOI: 10.1016/j.genrep.2020.100740
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 target: A specific target for novel coronavirus detection

Abstract: An ongoing outbreak of pneumonia associated with a novel coronavirus has been reported worldwide and become a global health problem; hence, the diagnosis and differentiation of this virus from other types of coronavirus is essential to control of the disease. To this end, the analysis of genomics data plays a vital role in introducing a stronger target and consequently provides better results in laboratory examinations. The modified comparative genomics approach helps us to find novel specific targets by compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 5 publications
0
23
0
2
Order By: Relevance
“…The most accurate investigation on individuals who are infected by Covid19, is using molecular methods such as Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) and digital PCR droplets (ddPCR) (28) and Real Time Polymerase Chain Reactions (realtime PCR) (29)(30). RT-PCR has sensitive results, but ddPCR also has good potential for detecting blood samples (28). Clinical specimens that used are nasal secretions, blood, sputum, and bronchoalveolar lavage (BAL) in individuals who are suspected of being infected with Covid19 (14).…”
Section: Discussionmentioning
confidence: 99%
“…The most accurate investigation on individuals who are infected by Covid19, is using molecular methods such as Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) and digital PCR droplets (ddPCR) (28) and Real Time Polymerase Chain Reactions (realtime PCR) (29)(30). RT-PCR has sensitive results, but ddPCR also has good potential for detecting blood samples (28). Clinical specimens that used are nasal secretions, blood, sputum, and bronchoalveolar lavage (BAL) in individuals who are suspected of being infected with Covid19 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Kakhki et al . proposed that ORF8 might serve as an excellent detection target as its sequence contains stretches of nucleotides that are wholly unique to SARS-CoV-2 [ 94 ].…”
Section: Nonstructural Proteinsmentioning
confidence: 99%
“…ORF8b is found to form cellular aggregates and induces cell death through ER stress and robust activation of the NLRP3 inflammasome (Shi et al, 2019). Very recently, the ORF8 gene has been considered as a novel target for identifying COVID-19 disease (Kakhki et al, 2020). Besides this, it has been demonstrated that the E protein of SARS-CoV also elicits an immune response to produce apoptosis of FIGURE 2 | Schematic representation of how coronavirus disrupts signaling pathways (autophagy, ER stress, cytokine storm, and hypoxia) and induces cell death.…”
Section: Sars-cov Induces Cellular Stress and Apoptosismentioning
confidence: 99%